Properties of strong random operators generated by an Arratia flow - Korenovskaya, Ya. A.; Кореновская, Я. А.; Кореновская, Я. А. (Institute of Mathematics, NAS of Ukraine, 2017)
We study the properties of strong random operators $T_t$ in $L_2(R)$ used to describe the shifts of the functions along an Arratia flow. We prove the formula of change of variables for the Arratia flow. As a consequence of this formula, we establish sufficient conditions for compact sets $K \subset L_2(R)$ under which $T_t$ has a continuous modification on $K$. We also present necessary and sufficient conditions for the convergent sequences in $L_2(R)$ under which the operator $T_t$ preserves their convergence.